2010
DOI: 10.1142/s0217751x10049839
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization Group Evolution of Neutrino Masses and Mixing in Seesaw Models

Abstract: We consider different extensions of the standard model which can give rise to the small active neutrino masses through seesaw mechanisms, and their mixing. These tiny neutrino masses are generated at some high energy scale by the heavy seesaw fields which then get sequentially decoupled to give an effective dimension-5 operator. The renormalization group evolution of the masses and the mixing parameters of the three active neutrinos in the high energy as well as the low energy effective theory is reviewed in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…The renormalization group (RG) evolution of neutrino parameters has recently been reviewed in 173 . If some unknown high energy theory at a scale Λ leads to a mass matrix m 0 ν , then in the effective theory one has the following mass matrix at low scale λ, where measurements take place:…”
Section: Renormalizationmentioning
confidence: 99%
“…The renormalization group (RG) evolution of neutrino parameters has recently been reviewed in 173 . If some unknown high energy theory at a scale Λ leads to a mass matrix m 0 ν , then in the effective theory one has the following mass matrix at low scale λ, where measurements take place:…”
Section: Renormalizationmentioning
confidence: 99%
“…As is well known, the effective neutrino mass matrix, M ν , is sensitive to the effect of the running of the mass matrix parameters from high to low energy [72,73]. Actually, small mixing angles could get a notable enhancement, as remarked in [72].…”
Section: The Masses Of Right-handed Neutrinos Without Degenerationmentioning
confidence: 91%
“…In the supersymmetric theories with a large tan β, it has been found that the RG evolution may lead to significant modifications to the mixing parameters, in particular the solar mixing angle θ 12 (see e.g., Ref. [12] and references therein). To be explicit, we write down the RGE's for neutrino mixing angles in the MSSM in the leadingorder approximation [13], • is assumed at the high-energy scale, the RG effects will lead to an even larger θ 12 at the low-energy scale, which may be in conflict with current oscillation data [14].…”
Section: Radiative Correctionsmentioning
confidence: 99%